FENOMENA BULLYING VERBAL DI SEKOLAH DASAR (STUDI KASUS) - Rizky Ade Kurniawan; Yantoro; Faizal Chan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research explains the phenomenon of Verbal bullying cases in elementary schools (Case Study). This research was conducted at SD Negeri 111/IX Muhajirin class V. This research was conducted in even semester. The approach used in this research is a qualitative approach. Qualitative approach is a research approach that finds a particular situation through verbal descriptions of accurate and realistic results based on relevant natural data collection techniques. The results showed: Verbal bullying in SD Negeri 111/IX Muhajirin is caused by differences in age, physique, character and background of students. Bullying handling that has been carried out at SD Negeri 111/IX Muhajirin includes enforcing discipline in handling and preventing bullying, mental coaching for students (especially bullying perpetrators and victims), supervision for students so that bullying does not recur, class teacher strategies (achievement cards, achievement reports) in handling bullying and cooperation with parents. The characteristics of bullying perpetrators in general, among others, tend to be active, low academic ability, quiet but easily emotional, physically larger, senior. While the characteristics of victims of bullying include being more quiet, slow learners, timid, female students are also more likely to be victims of weaker nature, and not good students in class, younger age.In addition, there is a tendency that victims can potentially become perpetrators and vice versa.